PERANCANGAN KEMASAN USAHA RENDANG BOLA-BOLA UNI SOFIE BUKITTINGGI - HANSRIAN ZURIHNAL, Dini Faisal, S.Ds., M.Ds., Dra. Zubaidah, M.Sn. (DEKAVE : Jurnal Desain Komunikasi Visual, 2018)
Rendang is a dish with processed meat from Minangkabau. Each region is unique when processing Rendang. The home business of the Uni Sofie, which is located in Bukittinggi, processes tuna meat into Rendang. Fish meat is ground, and made round like meatballs. The preparation is called